2014
DOI: 10.1002/anie.201403968
|View full text |Cite
|
Sign up to set email alerts
|

Cyclizing Radical Carboiodination, Carbotelluration, and Carboaminoxylation of Aryl Amines

Abstract: Radical carboiodination of various aryl amines is reported. Aryl diazonium salts, generated in situ from the corresponding aryl amines, are reacted with Bu4NI to provide the corresponding aryl radicals which undergo 5-exo or 6-exo cyclization. Iodine abstraction eventually affords the carboiodinated products in good to excellent yields. If TEMPO is added, the cascade provides the cyclized carboaminoxylation products. Running the reaction in the presence of PhTeTePh affords the phenyltellurated cyclized product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 43 publications
1
24
0
2
Order By: Relevance
“…1‐(Allyloxy)‐2‐nitrobenzene (3i) Light yellow oil (conditions A: 46 mg, yield 51 % ) or (conditions B: 47 mg, yield 52 % ), (46 mg, yield 51 %), flash chromatography eluting with petroleum ether/ethyl acetate (30:1). 1 H NMR (CDC1 3 , 400 MHz) 7.84 (dd, J = 8.1 Hz, 1.6 Hz, 1H), 7.53–749 (m, 1H), 7.08 (d, J = 8.4 Hz, 1H), 7.05–7.01 (m, 1H), 6.09–5.99 (m, 1H), 5.51–5.47 (m, 1H), 5.35–5.32 (m, 1H), 4.70–4.68 (m, 2H).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1‐(Allyloxy)‐2‐nitrobenzene (3i) Light yellow oil (conditions A: 46 mg, yield 51 % ) or (conditions B: 47 mg, yield 52 % ), (46 mg, yield 51 %), flash chromatography eluting with petroleum ether/ethyl acetate (30:1). 1 H NMR (CDC1 3 , 400 MHz) 7.84 (dd, J = 8.1 Hz, 1.6 Hz, 1H), 7.53–749 (m, 1H), 7.08 (d, J = 8.4 Hz, 1H), 7.05–7.01 (m, 1H), 6.09–5.99 (m, 1H), 5.51–5.47 (m, 1H), 5.35–5.32 (m, 1H), 4.70–4.68 (m, 2H).…”
Section: Methodsmentioning
confidence: 99%
“…The products were characterized by 1 H NMR, 13 C NMR, MS or HRMS. [15] [16] [16] [17] [18] [18] Light green oil (con-…”
Section: Methodsmentioning
confidence: 99%
“…For example, Carrillo and co‐workers reported that ascorbic acid can act as an appropriate initiator in intermolecular C−H arylation of arenes with anilines . In addition, iodide, benzoyl peroxide (BPO), and porphyrin have been identified as efficient initiators to generate aryl radicals from aryl diazonium salts. Inspired by these precedents, we initially studied the radical translocation of readily prepared o ‐aminobenzamide 1 a with methanol ( 2 a ) in the presence of n Bu 4 NI as an initiator and t BuONO as a nitrosating agent at room temperature under N 2 for 3 h. Interestingly, the desired product 3 aa was isolated in 6 % yield (Table , entry 1).…”
Section: Methodsmentioning
confidence: 99%
“…Nonetheless, there are still some restrictions including 1) relatively high reaction temperatures, 2) special and expensive ligands, and 3) the required absence of a β‐H next to the iodine. In 2014, Studer and coworkers reported another elegant Sandmeyer‐type protocol to synthesize intermediate IV . In their report, they employed an in situ generated diazonium salt as the key reactant species, which could be reduced by the iodide to form the phenyl radical.…”
Section: Figurementioning
confidence: 99%
“…In 2014, Studer andc oworkers reported another elegantS andmeyer-type protocol to synthesize intermediate IV. [9] In their report, they employed an in situ generated diazonium salt as the key reactants pecies, which could be reduced by the iodide to form the phenyl radical. Due to the favorable intramolecular ring closure, the phenyl radical can be trapped by the double bonds to form the desired rings.…”
mentioning
confidence: 99%